A review of marketing strategies from the European chocolate industry - Nur Suhaili Ramli (Journal of Global Entrepreneurship Research, 2017)
This paper reviews the main marketing strategies applied by the European chocolate industry. It focuses on the role of country-of-origin, product diversification and scenarios, and provides a historical overview of the industry. This is followed by a discussion of the association between a brand and country-of-origin, before scrutinising the chocolate industry. The analysis of this study uses evidence gathered from the consumer chocolate ranking, company annual reports, consultant statistics, corporate websites and the newspaper archives. The analysis compares the marketing strategies of case studies selected; namely, Ferrero Rocher, Cadbury, Lindt and Sprüngli and Godiva. Moreover, emphasis is placed on the similarities and differences of these brands and other chocolate brands outside Europe. The study's existing literature and analysis suggests that historical context and business history play important roles over time.
Keywords: 650; Chocolate industry; Marketing strategies; Global brands; Qualitative research; Europe